Oil rents, economic growth, and CO2 emissions in 13 OPEC member economies: Asymmetry analyses - Mahmood, Haider; Saqib, Najia (Frontiers in Environmental Science, 2022)
Oil rents significantly contribute to income in OPEC member economies and could have environmental consequences. The present study explores the asymmetrical effects of oil rents on CO2 emissions in 13 current OPEC economies using a period 1970–2019, and also tests the Environmental Kuznets Curve (EKC) hypothesis. Long-run results show that economic growth has a positive effect, and its square term has a negative effect on CO2 emissions in Algeria, Congo, Gabon, Kuwait, and Saudi Arabia, which validate the EKC in these countries. However, a U-shaped effect of income growth on emissions is substantiated in Angola. Moreover, rising oil rents have positive effects on CO2 emissions in Saudi Arabia, Angola, Congo, Equatorial Guinea, Iran, Iraq, Kuwait, and Libya, and have negative impacts in Algeria, Nigeria, and the UAE. Decreasing oil rents reduce CO2 emissions in Angola, Equatorial Guinea, Libya, and Saudi Arabia, and increase emissions in Algeria. Moreover, asymmetrical effects of oil rents on emissions are found in Angola, Congo, Iran, Iraq, Kuwait, Nigeria, Equatorial Guinea, Saudi Arabia, and the UAE. The short-run results show that the EKC is validated in Algeria, Congo, and Libya. However, economic growth shows a monotonic positive impact on emissions in Nigeria, the UAE, and Venezuela. Increasing oil rents show a positive impact on emissions in Angola, Congo, Iran, and Kuwait and carry a negative impact in Algeria and the UAE. In addition, decreasing oil rents increase CO2 emissions in Algeria, Gabon, Nigeria, and Saudi Arabia. We recommend Angola, Congo, Equatorial Guinea, Iran, Iraq, Kuwait, Libya, and Saudi Arabia to adopt tight environmental policies in times of increasing oil rents to avoid the negative environmental consequences of oil rents.